Pengembangan Aerospace Park di Indonesia berdasarkan Potensi Pergerakan Pesawat Udara - Jaka Yanuwidiasta (Research and Development Agency of The Ministry of Transportation, 2014)
One of the supporting industries that has high development in line With the rapid growth of aviation services in Indonesia the business Of aircraft including the procurement and production of spare parts and overhaul including the procurement and production of spare parts and the provision of supporting human resources. In 2012, there were 30 business entities engaged in the business of and aircraft is incorporated in IAMSA (Indonesian Aircraft Maintenance Shop Association). The purpose of this research was to obtain an overview of potential development of the Aerospace Park in Indonesia and find alternative airport that could be developed as an Aerospace Park in Indonesia. Based on the potential movement of aircraft and land availability, it is proposed to develop Aerospace Park in Soekarno Hatta Jakarta, Hussein Sastranegara Bandung, Kertajati Majalengka, Juanda Surabaya, Sultan Hasanuddin Makassar, Sam Ratulangi Manado, Sentani Jayapura, Segun Sorong, Hang Nadim Batam, Raja Fisabilillah Tanjung Pinang. Smarinda Baru, Tjilik Riwut Palangkaraya dan BIL Lombok. Salah satu industri pendukung yang sangat berkembang sejalan dengan pesatnya pertumbuhan jasa penerbangan di Indonesia adalah bisnis pemeliharaan dan perawatan pesawat udara termasuk pengadaan dan produksi suku cadangnya serta penyediaan SDM pendukungnya. Pada tahun 2012, tercatat 30 badan usaha yang bergerak dalam bisnis perneliharaan dan perawatan pesawat udara yang tergabung dalam IAMSA (Indonesian Aircraft Maintenance Shop Association). Tujuan penelitian ini adalah untuk mendapatkan gambaran pengembangan Aerospace Park di Indonesia dan mengetahui alternatif bandar udara yang bisa dikembangkan sebagai Aerospace Park di Indonesia. Berdasarkan potensi pergerakan pesawat udara dan faktor ketersediaan lahan diusulkan pengembangan Aerospace Park di Bandar Udara Soekarno Hatta Jakarta, Hussein Sastranegara Bandung, Kertajati Majalengka, Juanda Surabaya, Sultan Hasanuddin Makassar, Sam Ratulangi Manado, Sentani Jayapura, Segun Sorong, Kualanamu Medan, Hang Nadim Batam, Raja Fisabilillah Tanjung Pinang_ Samarinda Baru, Tjilik Riwut Palangkaraya dan BIL Lombok.